Habitat requirement analyses can guide pest rodent management in oil palm plantations: Evidence from Sabah, Malaysia - Asrif, Nur Athirah; Hafidzi, Mohd Noor; Burhanuddin, Maisarah; Azhar, Badrul (Elsevier Ltd, 2025)
Pest rodents consistently inflict substantial financial losses on the Southeast Asian oil palm industry, underscoring the critical need for effective management strategies to sustain these vital plantations. While chemical rodenticides have been a common tool, commercial growers seldom adopt ecologically based approaches. This study employed habitat requirement analysis using small mammal traps to guide more ecological pest management practices. Our findings indicate that the diverse structural and resource characteristics linked to different oil palm stand ages directly impact rodent abundance and body weight, thus supporting the necessity of ecologically informed management. Predictive modelling identified planted fields as the primary source of captured rodents, with lower numbers in housing and riverine areas, highlighting planted fields as key targets for effective pest control. Furthermore, our research revealed differential body weight patterns among rodent species, as plantation habitat alone did not significantly influence the weight of dominant species (Rattus rattus diardii and Rattus argentiventer). These observations emphasize the importance of considering species-specific behaviors and habitat preferences when implementing pest control strategies in oil palm plantations. Overall, this study highlights the value of prolonged trapping efforts, particularly in mature stands, as an effective and ecologically sound tool for managing pest rodent populations, while acknowledging the ecological factors contributing to body weight variations across habitat types. Understanding these habitat requirements is crucial for managers to make better-informed decisions regarding the spatial and temporal allocation of pest control efforts, and rodent trapping aligns with environmental sustainability principles by reducing reliance on chemical interventions.